Mast Cells in Gastrointestinal Disease - Ramsay, David B. (Millennium Medical Publishing, 2010)
The function of mast cells in allergic inflammatory reactions is well documented in the literature. Mast cells also play an important role in the regulation of gastrointestinal visceral sensitivity and vascular permeability. Several studies have noted an increased number of mast cells in the mucosa of patients with gastrointestinal diseases such as irritable bowel syndrome, mastocytic enterocolitis, and systemic mastocytosis. The role of mast cells in the symptomatology of these and other diseases has only recently been fully appreciated and could provide avenues for new therapeutic opportunities. This paper examines studies that have evaluated the role of mast cells in various gastrointestinal diseases.